Performance evaluation of embedded ethernet and Controller Area Network (CAN) in real time control communication system - Ching Chia Leong; Mohamad Khairi Ishak (Institute of Advanced Engineering and Science, 2019)
Real-time communication is important in control network. In real-time communication, message need to be delivered from source to destination within specification. Embedded Ethernet and Controller Area Network (CAN) protocol can be used in control network to achieve hard real-time communication. For embedded Ethernet protocol, Carrier Sense Multiple Access with Collision Detection (CSMA/CD) is the media access control (MAC) used to control data transmission between nodes in network. Back-off algorithm in CSMA/CD is used to handle packet collisions and retransmission. For CAN protocol, it is communication protocol developed mainly for automotive application. It has priority arbitration to handle collisions and retransmission. In this project, embedded Ethernet network models and CAN network models are developed and simulated in MATLAB Simulink software. Several back-off algorithms, which are Binary Exponential Backoff (BEB), Linear Back-off Algorithm, Exponential-Linear back-off Algorithm and Logarithm Back-off Algorithm are proposed and implemented into Embedded Ethernet network model to evaluate the performance. Both embedded Ethernet and CAN network models are extended to 3 nodes, 10 nodes, and 15 nodes to evaluate performance at different network condition. The performance criteria evaluated and discussed are average delay and jitter of packets. The results show that in network with high number of nodes, Linear Back-off Algorithm and Exponential-Linear back-off Algorithm shows improvement in packets delay and jitter. For CAN network, the packet jitter is relatively low.